2016
DOI: 10.1021/acs.jproteome.6b00235
|View full text |Cite
|
Sign up to set email alerts
|

Native Piezo2 Interactomics Identifies Pericentrin as a Novel Regulator of Piezo2 in Somatosensory Neurons

Abstract: The ability of somatosensory neurons to perceive mechanical stimuli relies on specialized mechanotransducing proteins and their molecular environment. Only recently has the identity of a major transducer of mechanical forces in vertebrates been revealed by the discovery of Piezo2. Further work has established its pivotal role for innocuous touch in mice. Therefore, Piezo2 offers a unique platform for the molecular investigation of somatosensory mechanosensation. We performed a mass spectrometry-based interacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 60 publications
(201 reference statements)
4
48
0
Order By: Relevance
“…In 2006, McCarter et al found that non‐specific cation influx mediated RA currents, while PIEZO2 has been identified to be the molecular basis for mediating RA currents in DRG neurons . In our study, the RA current induced by mechanical stimulation could be significantly blocked by the specific PIEZO2 blocker, FM1‐43.…”
Section: Discussionsupporting
confidence: 53%
“…In 2006, McCarter et al found that non‐specific cation influx mediated RA currents, while PIEZO2 has been identified to be the molecular basis for mediating RA currents in DRG neurons . In our study, the RA current induced by mechanical stimulation could be significantly blocked by the specific PIEZO2 blocker, FM1‐43.…”
Section: Discussionsupporting
confidence: 53%
“…However, our analysis has not been exhaustive as we did not examine all splice variants of Piezo2 and we did not investigate the potential interaction of Piezo2 with other membrane proteins. Other intracellular signaling pathways (Borbiro et al, 2015;Dubin et al, 2012) and protein interactions (Narayanan et al, 2016;Poole et al, 2014) have been shown to modulate Piezo2 function. More importantly, to fully appreciate the contribution of receptor diversification, it will be important to determine the in vivo consequences of Piezo2 splicing.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis has not been exhaustive as we did not examine all splice variants of Piezo2 and we did not investigate the potential interaction of Piezo2 with other membrane proteins. Other intracellular signaling pathways (Borbiro et al, 2015; Dubin et al, 2012) and protein interactions (Narayanan et al, 2016; Poole et al, 2014) have been shown to modulate Piezo2 function. More importantly, to fully appreciate the contribution of receptor diversification, it will be important to determine the in vivo consequences of Piezo2 splicing.…”
Section: Discussionmentioning
confidence: 99%